Eski ve güncel sermaye piyasası mevzuatı ve meslek kurallarının karşılaştırılması - Aliyeva, Mujgan (My University, 2018)
ÖZETDünya üzerinde sermaye piyasaları fon sahipleri ile fon talep edenleri bir araya getiren önemli bir mekanizma olmuş ve bu sebepten dolayı her geçen gün daha fazla büyüyen bir yapı halini almıştır. Bununla birlikte, sermaye piyasası mensuplarının uyacakları davranış şeklini gösteren meslek kuralları, piyasanın güven, açıklık, istikrar içinde çalışması adına önem arz etmektedir.Türkiye’de 1981 yılında yürürlüğe giren 2499 sayılı Sermaye Piyasası Kanunu yaptırımlar ve uygulanabilirlik açısından yetersiz hale gelmiş ve bu sebep ile ortaya çıkan ihtiyacı karşılamak için 6362 sayılı yeni Sermaye Piyasası Kanunu yürürlüğe girmiştir.Çalışmada sermaye piyasasının temel kavramları hakkında bilgi verilmiş, daha sonra eski Sermaye Piyasası Kanunu ve güncel hali incelenmiştir. Ayrıca sermaye piyasası meslek kuralları da eski ve güncel şekliyle değerlendirilmiştir.Çalışmada son olarak; eski kanun ile güncel kanun arasında karşılaştırmalar yapılmış ve aradaki farklar ortaya koyulmuştur. Çalışma neticesinde, eski kanunun caydırıcı yaptırımların uygulanması konusunda yetersiz kaldığı konusundaki hipotez genel anlamda doğrulanmaktadır.Sermaye Piyasası, 2499 sayılı Sermaye Piyasası Kanunu, 6362 sayılı Sermaye Piyasası Kanunu, Meslek Kuralları. COMPARISON OF OLD AND CURRENT CAPITAL MARKET LEGISLATION AND CODE OF PRACTICESSUMMARYCapital markets on the world have become an important mechanism bringing together fund holders and fund claimants and because of this reason it has become a constitution that grows more and more every day. However, code of practices which show behavioral way of members of the capital market are important for the market to work in confidence, openness and stability. The Capital Market Law no. 2499 entered in force which in 1981 in Turkey, has become insufficient in terms of sanctions and applicability and the new Capital Market Law no. 6362 has entered into force in order to meet the need arising from this reason. In the study, it has been informed about the basic concepts of capital market, then the old Capital Market Law and the current version of it have been examined. In addition, the capital market code of practices have been evaluated with the style of an old and current.Finally, it has been made comparisons between the old law and the current law in the study and the differences have been revealed. As a result of the study, the hypothesis that the old law is inadequate about implementation of deterrent sanctions is verified in general terms.

COMPARISON OF OLD AND CURRENT CAPITAL MARKET LEGISLATION AND CODE OF PRACTICESSUMMARYCapital markets on the world have become an important mechanism bringing together fund holders and fund claimants and because of this reason it has become a constitution that grows more and more every day. However, code of practices which show behavioral way of members of the capital market are important for the market to work in confidence, openness and stability.The Capital Market Law no. 2499 entered in force which in 1981 in Turkey, has become insufficient in terms of sanctions and applicability and the new Capital Market Law no. 6362 has entered into force in order to meet the need arising from this reason.In the study, it has been informed about the basic concepts of capital market, then the old Capital Market Law and the current version of it have been examined. In addition, the capital market code of practices have been evaluated with the style of an old and current.Finally, it has been made comparisons between the old law and the current law in the study and the differences have been revealed. As a result of the study, the hypothesis that the old law is inadequate about implementation of deterrent sanctions is verified in general terms.
Keywords: Capital market; Capital Market Law no. 2499; Capital Market Law no. 6362; Code of Practices; Law and legislation; Sermaye piyasası; Yasa ve yasam